2020
DOI: 10.1111/1462-2920.15290
|View full text |Cite
|
Sign up to set email alerts
|

T4‐like myovirus community shaped by dispersal and deterministic processes in the South China Sea

Abstract: Summary As the most abundant and genetically diverse biological entities, viruses significantly influence ecological, biogeographical and evolutionary processes in the ocean. However, the biogeography of marine viruses and the drivers shaping viral community are unclear. Here, the biogeographic patterns of T4‐like viruses and the relative impacts of deterministic (environmental selection) and dispersal (spatial distance) processes were investigated in the northern South China Sea. The dominant viral operationa… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

1
21
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
5

Relationship

2
3

Authors

Journals

citations
Cited by 7 publications
(22 citation statements)
references
References 86 publications
1
21
0
Order By: Relevance
“…The most abundant T4-like viruses of the Chinese estuarine ecosystems belonged to MG, which could be further subdivided into five MG subgroups (I to V) and two subgroups of Exo-T-even viruses that were predicted to infect cyanobacteria (Exo-T-evens–I and Exo-T-evens–II). Previous studies showed that MG I and MG IV had wide geographical distributions, whereas MG II, MG III, and MGV were abundant in low-salinity eutrophic environments ( 9 , 17 ). Sequences of the Exo-T-evens–I group were more closely related to the g23 genes of isolated cyanophages.…”
Section: Resultsmentioning
confidence: 98%
See 4 more Smart Citations
“…The most abundant T4-like viruses of the Chinese estuarine ecosystems belonged to MG, which could be further subdivided into five MG subgroups (I to V) and two subgroups of Exo-T-even viruses that were predicted to infect cyanobacteria (Exo-T-evens–I and Exo-T-evens–II). Previous studies showed that MG I and MG IV had wide geographical distributions, whereas MG II, MG III, and MGV were abundant in low-salinity eutrophic environments ( 9 , 17 ). Sequences of the Exo-T-evens–I group were more closely related to the g23 genes of isolated cyanophages.…”
Section: Resultsmentioning
confidence: 98%
“…This indicated a large body of uncharacterized T4-like viruses in nature. All of the g23 OTUs obtained in Chinese estuaries, the representative g23 genes from different environments (e.g., marine, estuary, lake, paddy) ( 9 , 12 , 17 , 21 , 22 ), and the g23 genes of isolated T4-like phages in the NCBI NR database were used to build a phylogenetic tree. Overall, the phylogenetic profiles of the g23 genes formed three distinct clusters, which are referred to as Clusters I to III ( Fig.…”
Section: Resultsmentioning
confidence: 99%
See 3 more Smart Citations